Emotional exhaustion and academic performance in university students when returning to face-to-face classes - Ibarra Aguirre, Enrique; Ibarra Lizárraga, Elizabeth; Sánchez Guzmán, Yeshica Ludim (IE Revista de Investigación Educativa de la REDIECH, 2024)
This study aimed to (1) describe the emotional fatigue of university students during their return to the university in person, (2) identify the differences by sex and between those who combine study and work and those who only study, and (3) analyze the correlation between emotional fatigue and academic performance. It is a quantitative study, where an incidental sample of 240 students participates; 78.8% (189) were women and 22.2% (51) men, of which 47.5% (114) work and study and 52.5% (126) only dedicate themselves to studying. The Emotional Exhaustion Questionnaire was administered, plus a sociodemographic one to investigate sex, age and whether they work and study, and their grade averages were used. It was found that the level of emotional exhaustion of the students ranges from low to moderate. Women have higher scores than men, without significant differences. Those who study and work get significantly more emotionally exhaustion than those who only study. There is an inverse relationship between emotional exhaustion and academic performance. It is necessary to delve deeper into this area of study and address differences by sex and those who combine school and work.